MATURITY MEASUREMENT ON BIGEYE SCAD (Selar crumenophthalmus BLOCH 1793) TO INDICATE OVERFISHING - Grace Hutubessy (Indonesian Fisheries Research Journal, 2021)
Bigeye scad (Selar crumenophthalmus) is one of the small pelagic economical species from the family of Carangidae. The annual landing of Carangids in Ambon Island sharply dropped in 2018. Meanwhile, demand for these fish has increased following the local population growth. Was the reduction of fish products showing an indication of overfishing? To answer this, we measured the maturity of bigeye scad caught in Ambon waters during east monsoon (May to July 2019 and March to June 2020), including the length-frequency distribution. We found that the minimum size was 5 cm, the maximum (Lmax) was 23 cm, and the optimum length (Lopt) was 18.7 cm. The estimated length of first maturity (Lm) of bigeye scad was 18.3 cm. This study showed that the optimum length was slightly longer than maturity length. Less than 30% of the catch of bigeye scad was immature and indicated a small probability of recruitment overfishing. Arround 57% of megaspawner found during this study showed more robust broodstocks to produce survival larvae into the population. The possibility of overfishing is relatively low for the bigeye scad fishery during the east monsoon, except for the reduction in the maturity size should be concerned.